How embedded lead users can contribute to innovation process: A systematic literature review - Anna Laitio; Satu Nätti (Journal of Innovation Management, 2023)
Embedded lead users (ELUs) are ﬁrm employees who are also users of the ﬁrm’s products, holding that role most often due to their active participation in their spare time in the user domain. ELUs are able to integrate knowledge of customer needs in the innovation process based on their social contacts, user experiences, and knowledge of the innovating network or organization, for example. Due to this ability ELUs can facilitate innovation processes. The aim of this systematic literature review is to examine how according to the existing literature ELUs can contribute to different stages of the company innovation process. Three research questions are answered. 1) What kind of resources can ELUs offer for the innovation process? 2) How and based on which resources do ELUs contribute to the different stages of the innovation process? 3) What kinds of roles do ELUs have and how does their dual role in the user domain and the company influence the innovation process? Findings of the study bring new managerial perspectives on how companies can utilize ELUs in their innovation practices. In addition, by forming a holistic picture of current ELU research, this paper offers a variety of theoretical contributions in the form of holistic description of ELUs role in the innovation process in its different stages.